LIQUID SOAP FORMULATION FROM ETHANOLIC EXTRACT OF CASSAVA LEAVES (Manihot esculenta Crantz) WITH COCAMIDE DEA AS SURFACTANT - Nooryza Martihandini; Diani Putria Angelica; Shandra Isasi Sutiswa (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
The ethanol extract of cassava leaves contains various secondary metabolites that have antibacterial activity against Escherichia coli, Staphylococcus aureus, and Shigella sp., and thus can be used as active ingredients in liquid soap preparation. Liquid soap formulations generally use sodium lauryl sulfate (SLS) as a surfactant, which can cause irritation and skin dryness. This study aimed to formulate an ethanol extract from cassava leaves into a liquid soap preparation using cocamide DEA as a surfactant to reduce skin irritation. The study was conducted in an experimental laboratory. Cassava leaves were extracted by maceration using ethanol. Three liquid soap formulas from cassava leaf extract were developed with different extract concentrations: F1 (1%), F2 (3%), and F3 (5%). The liquid soaps were evaluated in terms of organoleptic properties, pH, homogeneity, viscosity, foam height, and foam stability. The study showed that cassava leaves extract could be formulated into a homogeneous liquid soap with a pH range of 7.0–7.5, viscosity of 143.6–306.2 cps, foam height of 53.33–60.00 mm, and foam stability of 75.01–82.36%. F3 is the optimum formula with the best physical characteristics of the preparation in terms of organoleptic properties, foam height, and foam stability. Keywords: cocamide DEA, cassava leaves, liquid soap, surfactant